2019
DOI: 10.3390/ijerph16060952
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic Impact Analysis of Multi-Dimensional Indicators of Streetscape Fabric in the Medium Spatial Zone

Abstract: Different historical backgrounds and planning ideas have created different urban streetscape fabrics. The patterns of the streetscape fabric have affected urban microclimate factors and formed a unique local microclimate. This paper simulated the microclimatic effects in four study areas with different streetscape fabrics in Shanghai to compare the microclimatic conditions with a system of multi-dimensional street morphological indices using ENVI-met 4.3 software. At the street network fabric level, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Through the analysis of CV value changes of three green corridor patterns, it can be seen that the fluctuation variation effect of air temperature with the various spatial types of green corridors at the holistic block level. The formula for calculating coefficient of variation is as follows [47]:…”
Section: The Thermal Variables For Describing Cooling Effectmentioning
confidence: 99%
“…Through the analysis of CV value changes of three green corridor patterns, it can be seen that the fluctuation variation effect of air temperature with the various spatial types of green corridors at the holistic block level. The formula for calculating coefficient of variation is as follows [47]:…”
Section: The Thermal Variables For Describing Cooling Effectmentioning
confidence: 99%
“…With reference to the research on the photosynthetic characteristics and configuration of various dominant tree species in Shanghai [35,60], and combined with the distribution of each tree species, Platanus, Robinia, Cinnamomum, Privet, and Metasequoia were selected, respectively, and were constructed according to the actual landscape composition. Many scholars have used ENVI-met to conduct microclimate studies and verified the validity of the simulation results [61][62][63][64]. In this study, the simulation results of ENVI-met were compared with the observed values to verify the validation of the software on CO 2 concentration.…”
Section: Envi-met Dynamic Simulationmentioning
confidence: 83%
“…The MAPEs of temperature and relative humidity are less than 10% (Chow et al, 2011;Salata et al, 2017). The Indexes of Agreement (d) are between 0.92-0.98, indicating that ENVI-met has a high simulation accuracy of outdoor temperature and relative humidity (Jiang et al, 2019).…”
Section: Envi-met Model Evaluationmentioning
confidence: 97%